An Empirical Examination of Sell-Side Brokerage Analysts' Published Research, Concierge Services, and High-Touch Services. Issue 4 (8th August 2021) - Maber, David A.; Groysberg, Boris; Healy, Paul M.
Abstract: This paper uses a proprietary panel dataset to categorize and quantify the activities that sell-side brokerage analysts use to build and sustain their network of buy-side client relations. We then examine the marginal impact of these activities on key analyst outcome metrics identified by prior literature. Our findings highlight the importance of two previously unstudied client-service activities – high-touch phone calls and non-deal road shows – and suggest that analysts may face a tradeoff between producing accurate earnings research and increasing the values of key performance measures that gauge the strength of their network of client relations.